Konsep Dan Struktur Pengembangan Kurikulum SD/MI - Sukati . (LITERASI (Jurnal Ilmu Pendidikan), 2012)
The curriculum is an important instrument of education, because the curriculum is a guide in carrying out instruction which is conducted by teachers, principals or policy makers at higher levels. Along with the developed era which is marked by global of information and technology currenly, the managemant and curriculum development should be done at all levels including in primary education / Islamic primary education levels.In curriculum development, involving the various components or elements. Each component requires a proper and serious development, because of the unity, connectedness, and coherence between the various components of the curriculum is process for achieving educational goals. Key words: Curriculum development, various component